Short-term cryoprotectant-free cryopreservation at −20°C does not affect the viability and regenerative capacity of nanofat - Limido, Ettore; Weinzierl, Andrea; Ampofo, Emmanuel; Harder, Yves; Menger, Michael D.; Laschke, Matthias W. (Frontiers in Bioengineering and Biotechnology, 2024)
Nanofat is an autologous fat derivative with high regenerative activity, which is usually administered immediately after its generation by mechanical emulsification of adipose tissue. For its potential repeated use over longer time, we herein tested whether cryopreservation of nanofat is feasible. For this purpose, the inguinal fat pads of donor mice were processed to nanofat, which was i) frozen and stored in a freezer at -20°C, ii) shock frozen in liquid nitrogen with subsequent storage at -80°C or iii) gradually frozen and stored at -80°C. After 7 days, the cryopreserved nanofat samples were thawed and immunohistochemically compared with freshly generated nanofat (control). Nanofat frozen and stored at -20°C exhibited the lowest apoptotic rate and highest densities of blood and lymph vessels, which were comparable to those of control. Accordingly, nanofat cryopreserved at -20°C or control nanofat were subsequently fixed with platelet-rich plasma (PRP) in full-thickness skin defects within dorsal skinfold chambers of recipient mice to assess vascularization, formation of granulation tissue and wound closure by means of stereomicroscopy, intravital fluorescence microscopy, histology and immunohistochemistry over 14 days. These analyses revealed no marked differences between the healing capacity of wounds filled with cryopreserved or control nanofat. Therefore, it can be concluded that cryopreservation of nanofat is simply feasible without affecting its viability and regenerative potential. This may broaden the range of future nanofat applications, which would particularly benefit from repeated administration of this autologous biological product.